Gravity and trade in video on demand services - Annette Broocks; Zuzanna Studnicka (University College Dublin, UCD School of Economics, 2021)
We estimate the patterns of catalogue availability (extensive margin) and number of clicks per title (intensive margin) using a novel data set containing the information on Netflix catalogues and viewing across 20 countries. Our results show evidence of the gravity framework explaining both margins of Netflix watching. In particular, we find that Netflix users have a strong preference for domestic productions. Detailed information on film and TV show characteristics gives us a unique opportunity to estimate the importance of quality in determining the patterns of Netflix watching. Independent viewers' ratings and a title's age play a key role in explaining the number of clicks directed at a particular title. Finally, Netflix Original productions attract a disproportionately large number of clicks.
Keywords: F10; L82; Z10; 330; Netflix; subscription video on demand; gravity equation; services trade